NATIVE AND EXOTIC FISH SPECIES IN THE TIBER RIVER WATERSHED (UMBRIA – ITALY) AND THEIR RELATIONSHIP TO THE LONGITUDINAL GRADIENT - LORENZONI M. (Knowledge and Management of Aquatic Ecosystems, 2006)
In this study we examine the spatial variations in the fish communities in the Tiber River watershed, including both native and exotic species. Its main objectives were to assess the quality of fish communities of this area and to verify if factors of fish community disturbance are constant over the basin or if they change along the river gradient. The level of degradation was evaluated according to the ratio between the number of native fish species and total number of species (ZIC = Zoogeographic Integrity Coefficient). A total of 37 fish species was found, 13 native and 24 exotic (64.86%). Cyprinid is the prevailing family with 15 species (7 native, 8 exotic). The species most frequently introduced are cyprinids, followed by salmonids (4 species) and gobids (3 species). Of the 24 exotic species only 11 (45.83%) can be considered intentionally introduced by man: the proportion of intentionally introduced transplanted species (66.67%) is considerably higher than the translocated species (33.33%). There is a correlation between the longitudinal gradient of the river, the morphological evolution of the riverbed and decline in water quality. High ZIC values were related to higher elevation, greater slope and better water quality. As the size of the river increases the fish communities appear to be ever-more dominated by species of exotic origin, whose number progressively increases with the worsening of the water quality and downstream movement. The number of native species is the greatest in the middle reaches of the rivers, and decreases both upstream and downstream. Compared to the introduced species, the native species tend to stay upstream and are often the only species found in the headwaters. The number of introduced species increases downstream. We have also found differences among translocated and transplanted species: the first ones tend to favor the middle reaches of the rivers, while transplanted species seem to prefer the downstream sectors. In almost all cases, the sampling station immediately below an impoundment has the lowest ZIC values in comparison to the river stretches above the dam. Our preliminary results suggest that characteristics of fish community alterations depend on the type of river sector involved; the small rivers of the basin are a refuge zone for the native community and are currently of fundamental importance for maintaining biodiversity.